2020
DOI: 10.1177/0192636520911197
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Performance Appraisal Regulation: A Policy Case Analysis

Abstract: This article uses an analysis of the language used in the Teacher Performance Appraisal Technical Requirements Manual in Ontario to highlight some procedural issues. Arguably, the existence of flaws in the teacher evaluation system is not only limited to evaluation practices but is also embedded in evaluation regulations. Furthermore, the article provides a novel example of how a study of teacher evaluation systems can go beyond teachers’ perspectives of evaluation practices and can also consider teacher evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…Dandalt and Brutus analyzed the teacher evaluation problems in Ontario's technical requirements manual for teacher performance evaluation. Tey concluded that the defects in the teacher evaluation system are limited to the evaluation practice and embedded in the evaluation rules [8]. Kagema and Irungu jointly studied and investigated the impact of teacher performance evaluation on the performance of middle school teachers in Kenya.…”
Section: Introductionmentioning
confidence: 99%
“…Dandalt and Brutus analyzed the teacher evaluation problems in Ontario's technical requirements manual for teacher performance evaluation. Tey concluded that the defects in the teacher evaluation system are limited to the evaluation practice and embedded in the evaluation rules [8]. Kagema and Irungu jointly studied and investigated the impact of teacher performance evaluation on the performance of middle school teachers in Kenya.…”
Section: Introductionmentioning
confidence: 99%
“…Issues concerning teacher performance have been widely studied in the past (Ghazali & Nordin, 2019). Due to its' important role in improving the education quality, teacher performance problems constantly become a major concern among academia (Dandalt & Brutus, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In response to professional issues, universities implement various TPA mechanisms. For example, some universities use conventional TPA methods through paper-based surveys by distributing hard-copy of questionnaires to students Dandalt and Brutus [9], and Buchanan et al [10] or using a mobile-based application [11]. However, instead of rampant implementation of mobile apps to evaluate teaching performance, more research needs to be conducted to determine factors influencing students' continuance intention to use mobile apps for teaching performance evaluation.…”
Section: Introductionmentioning
confidence: 99%